The SuperApp Implementation in Business: Revolutionizing Business Operations for a Seamless Future - Minghai, Yang; Wenqing, Luo; Akbar Khan, Waqar; Nurhalim, Wahyu (Bincang Sains dan Teknologi, 2023)
SuperApp implementation has emerged as a game-changing strategy for businesses in the digital era. These all-in-one platforms integrate multiple services and functionalities within a single application, revolutionising how companies operate and interact with customers. This article explores the concept of SuperApp implementation in various industries and highlights its key features and benefits. From enhancing user experiences to building digital ecosystems and leveraging data insights, SuperApps have transformed sectors such as e-commerce, transportation, financial services, and food delivery. The article also discusses potential future developments, including personalised experiences, integration of emerging technologies, expansion into new industries, and global adoption. Embracing the SuperApp model empowers businesses to stay competitive, meet evolving customer expectations, and unlock new opportunities for growth and success in the digital age.